'Innovative Industrialised Buildings: Performance, Perceptions, and Barriers to Financing associated with Building Manufacturing' - Hargroves, Charlie; Newman, Peter; Green, Jemma (2016)
Most buildings are still constructed one brick or timber at a time, over lengthy periods on-site, much like ancient civilisations. This paper poses the question of whether the manufacture of buildings using digital and production line techniques from advanced manufacture can transform building to be less wasteful, quicker, more affordable, and more sustainable. This is an important question as the innovative industrialisation of buildings presents a significant opportunity for the building and construction sectors worldwide. Findings suggest that between 2011 and 2012 the economic output from the industrialised manufacture of buildings globally increased by a staggering 50% to just over US$90 billion, with nearly half of this manufactured in the AsiaPacific region. The paper points out that there is great potential for the manufacture of buildings to be harnessed to significantly strengthen both the building and manufacturing sectors. The research suggests that domestic building industries around the world will face strong international competition in the near future, especially as the quality of imported prefabricated and manufactured building offerings is increasing and the price is decreasing. However the transition to manufactured buildings must be undertaken in such a way as to harness a nations existing pool of skills and trades so as to allow workforce transitioning in a manner that strengthens industry. The paper highlights a number of challenges to upscaling building manufacture related to finance, insurance, and warranty structures, and presents potential options for overcoming such barriers. This paper presents findings of research undertaken as part of a Sustainable Built Environment National Research Centre (SBEnrc) in Australia in collaboration with the Cooperative Research Centre (CRC) for Low Carbon Living.